Crianças e infâncias da Amazônia paraense: achados sobre a região do Baixo Tocantins - SANTOS, Aíris Corrêa dos (2022)
The article deals with being a child in the Amazon of Pará, especially those that inhabit the region of Baixo Tocantins, in order to identify the plurality of contexts in which infants experience their childhoods when considering the educational challenges and guaranteeing the rights of boys and girls. The study, within the qualitative approach, of a bibliographic nature, based on dissertations and theses by the authors Andrade (2018), Corrêa (2018), Buecke (2019), Pojo (2017) and Silva (2005), who discuss the child subject, their childhoods and their children's productions passing through relationships in the school, family and community. We emphasize the approaches mentioned in the studies, which affirm children as active, active, creative subjects in the environment in which they live, even facing an Amazonian social reality marked by precarious living and schooling conditions for these subjects. They manage to give their own “children's worlds” contours, by building and sharing their social and cultural practices, which speak of the uniqueness of life in the Amazon. Furthermore, given the importance of understanding who the children are, it is necessary to invest in more studies in this approach, because in the reality of the Baixo Tocantins region, for example, there are few studies that discuss the subject, at the same time, there is still much to be done, learn about and with children. That said, it is possible to build educational practices in our region from other perspectives, embedded in children's production in its diversity of children and their childhoods.